Occupational accidents with exposure to biological material: Description of cases in Bahia - Técia Maria Santos Carneiro e Cordeiro; José Nunes Carneiro Neto; Mariana de Castro Brandão Cardoso; Amália Ivine Santana Mattos; Kionna Oliveira Bernardes Santos; Tânia Maria de Araújo (Universidade de Santa Cruz do Sul, 2016)
Background and Objective: This study is included in the field of public health in Brazil, in particular occupational health, by the occupational accidents with exposure to biological material consists of a preventable injury. Thus, the objective was to describe risk factors the of occupational accidents with exposure to biological material and the conduct postexposure adopted notified of cases in Notifiable Diseases Information System (SINAN) in the State of Bahia in 2012. Methods: This is a descriptive epidemiological study realized with data from the injuries of notifications SINAN in February 2013, the analysis was realized using descriptive statistics in absolute frequencies and relative. Results: The results indicate a higher occurrence of occupational accidents involving exposure to biological materials in Bahia in the female population (78.1%) and aged between 30-49 years (51.5%); the blood was fluid larger contact in accidents 75.2% by percutaneous (71.5%); post-exposure procedures were adopted in accordance recommended by the Ministry of Health; divers information were not fulfilled in the notifications and only 23.8% of Occupational Accidents Comunication (CAT) were issued. Conclusion: It is considered necessary to draw up strategies on occupational health and safety, consciousness of workers about the relevance of the measures adopted after occupational accidents with exposure to biological material and the training of professionals for case notification and research to fill all the fields of the notification form and also the issuance of CAT.